A RESEARCH STUDY ON PATTERN OF THORACO-ABDOMINAL INJURIES SUSTAINED IN FATAL ROAD TRAFFIC ACCIDENTS THAT OCCURRED IN ONGOLE DURING 2021 YEAR: AN AUTOPSY BASED STUDY (Journal of Forensic Medicine & Toxicology, 2023)
Road Traffic Accident (RTA) is one among the top 5 causes of morbidity and mortality in South-East Asian countries. Most common cause of blunt abdominal trauma in India is road traffic accidents including pedestrian accidents, abdominal blows, and fall from heights. This is an autopsy based study done on 157 Road Traffic Accident Cases which were brought to Mortuary of Government Medical College, Ongole, Andhra Pradesh for Postmortem Examination during the year 2021. This autopsy-based study is taken up to know the incidence of Road Traffic Accidents leading to death in Ongole Police Stations Jurisdictions. This study is also done to understand and analyze the incidence and role of Thoraco-abdominal injuries leading to death in road traffic accident victims. The Economic Cost of Road Accidents in India is 39 billion Dollars: Bosch. Every day, 1214 road accidents occur in India. In 2019, the total medical cost of road traffic accidents victims in India was 0.82–1.92 billion dollars. As per the World Health Organization (WHO), only 28 countries representing 449 million people have adequate laws that address all the five risk factors of Road Traffic Accidents - speed, drunk driving, helmets, seat belts and child restraints. Road traffic accident casualties bring about a great deal of human suffering in terms of social, medical and economic costs, and it is crucial we mitigate them.
Keywords: Road traffic accident; Thoraco-abdominal Injuries; Hemothorax; Mesenteric injury; Ribs Fracture